2017
DOI: 10.3807/copp.2017.1.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrathin Backlight Unit by Using a Tapered Light Guide Film Studied by Optical Simulation

Abstract: Optical structures of a tapered ultra-thin light guide film (LGF) were optimized by optical simulation for increasing coupling efficiency between light sources and the LGF. A serration pattern on the entrance side surface could provide a comparable coupling efficiency to that of the conventional LGF where a linear, asymmetric prism array was formed on the taper surface. Several micro-patterns were applied to the top and/or bottom surface of the LGF for achieving better luminance property, and it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Compared to a conventional BLM, the novel configuration achieved higher uniformity (of >90%). Kuo et al [ 25 ] determined that the optimal processing parameters in a reciprocal comparisons approach were a cooling time of 30 s, a mold temperature of 85 °C, a melt temperature of 250 °C, an injection speed of 195 mm/s, an injection pressure of 240 MPa, a packing pressure of 110 MPa, packing switching of 5 mm, and a packing time of 3 s. Joo and Ko [ 26 ] studied the micro-prism pattern negatively inscribed into an LGP’s bottom surface, which was found to be the most effective design. Xu et al [ 27 ] indicated that the luminance uniformity of a BLM depended on the microstructure distributed on the LGP’s bottom surface.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a conventional BLM, the novel configuration achieved higher uniformity (of >90%). Kuo et al [ 25 ] determined that the optimal processing parameters in a reciprocal comparisons approach were a cooling time of 30 s, a mold temperature of 85 °C, a melt temperature of 250 °C, an injection speed of 195 mm/s, an injection pressure of 240 MPa, a packing pressure of 110 MPa, packing switching of 5 mm, and a packing time of 3 s. Joo and Ko [ 26 ] studied the micro-prism pattern negatively inscribed into an LGP’s bottom surface, which was found to be the most effective design. Xu et al [ 27 ] indicated that the luminance uniformity of a BLM depended on the microstructure distributed on the LGP’s bottom surface.…”
Section: Introductionmentioning
confidence: 99%
“…The function of the BLU is to transform the light flux from the point or line source into the areal illuminator towards the LCD panel. Light is usually extracted from the LGP by the micro-optical structures and/or printed dots on the surface of the LGP [1][2][3][4][5][6][7][8]. Instead of modifying the surface of the LGP, several contributors have proposed the use of the scattering polymer, where the optical transmission particles inside the LGP work to extract the light [9][10][11].…”
Section: Introductionmentioning
confidence: 99%